On Finding Geodesic Equation of Two Parameters Binomial Distribution - Chen, William W.S. (Transactions on Engineering and Computing Sciences, 2019)
The purpose of this paper is to find a general form of the geodesic equation of the binomial distribution. Using Darboux’s theory we will set up a second order partial differential equation. Then we will apply the chain rule to transform the variable and rotate the axis to remove the interaction term, which will lead us to find the geodesic equation of binomial distribution. To illustrate how we can find such a geodesic equation in practice, we demonstrate by an example.